Physics is easy :Check it out / Siti Nurul’Ain Zaiton ... [et al.] - Zaiton, Siti Nurul’Ain; Onn, Munirah; Azman, Hairul Amiza; Mohamad, Saiful Najmee; Mohammad IIiyas, Siti Mariam (Universiti Teknologi MARA, Perak, 2020)
The aim of this innovation is to produce a physics activity book. The book is based on the syllabus of Fundamental of Physics, which is suitable for SPM, STPM, Matriculation and Diploma level students. Despite the many studies which have been conducted and many methods that have been introduced, the effectiveness remains localized. With the current curriculum, the students in higher learning education have limited contact hours with the instructors. This book can help to make the learning process more interesting and assist to improve students' conceptual understanding for each chapter. Questions are designed using crossword puzzles and free online platforms like Kahoot and Google Form. Questions on online platforms can be reached through QR Code included in the book. Crossword puzzle questions are an interesting and creative way to test their understanding of each chapter, meanwhile online platform methods could provide immediate feedback when students complete their tasks. This real-time interactive learning approach can provide our students with a positive boost and motivation. The activity also allows the student to go through the quizzes as many times without being penalised. It will give the student another platform that they could access anytime and chance to comfortably go through in understanding more about physics.